Penggunaan Ekstrak Daun Pepaya Sebagai Inhibitor Korosi Baja Karbon Dalam Lingkungan Crude Oil - Muhammad Libasut Taqwa; Irwan Irwan; Pardi Pardi (Jurnal Teknologi, 2021)
The study of papaya leaf extract as a carbon steel corrosion inhibitor in a crude oil environment has been investigated using a weight-loss method. The effects of papaya leaf extract concentrations and immersion time have been employed to investigate the corrosion rate, with a variation of papaya leaf extract concentrations of 0, 1, 2, 3, 4, and 5 % volume and immersion time of 1, 2, 3, 4 and 5 hours. The results showed that increasing papaya leaf extract concentrations decreased the corrosion rate of carbon steel in a crude oil environment. While the increase of immersion time enhances the carbon steel corrosion rate in a crude oil environment. The lowest rate of corrosion obtained was 4.0152 mpy using papaya leaf extract concentration of 5 % volume at 5 hours immersion time. The inhibition efficiency also increased with increasing concentrations of papaya extract and immersion time. The highest inhibition efficiency was 65.54% at the concentration of papaya leaf extract 5% vol. at 5 hours immersion time.